2020
DOI: 10.1007/s00392-020-01763-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety and patient-reported outcomes in index ablation versus repeat ablation in atrial fibrillation: insights from the German Ablation Registry

Abstract: Background Pulmonary vein isolation is an established strategy for catheter ablation of atrial fibrillation (AF). However, in a significant number of patients, a repeat procedure is mandatory due to arrhythmia recurrence. In this study, we report safety data and procedural details of patients undergoing index ablation versus repeat ablation in a registry-based real-life setting. Methods Patients from the German Ablation Registry, a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
4
6
0
Order By: Relevance
“…Moreover, we observe the same for stroke and MACCE [Mack 2019;Mäkikallio 2016;Popma 2019;Serruys 2009;Stone 2016]. Also, no patient in our SR-group suffered a complication, which are more likely to occur in interventional ablations (where it is around 0.5%, i.e., pulmonary vein injury or stenosis, phrenic nerve palsy, vena cava, or esophageal injury [Kany 2021;Rottner 2021;Zylla 2020]). In addition, only 0.3% of patients in the SR group had a pulmonary embolism.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, we observe the same for stroke and MACCE [Mack 2019;Mäkikallio 2016;Popma 2019;Serruys 2009;Stone 2016]. Also, no patient in our SR-group suffered a complication, which are more likely to occur in interventional ablations (where it is around 0.5%, i.e., pulmonary vein injury or stenosis, phrenic nerve palsy, vena cava, or esophageal injury [Kany 2021;Rottner 2021;Zylla 2020]). In addition, only 0.3% of patients in the SR group had a pulmonary embolism.…”
Section: Discussionsupporting
confidence: 69%
“…In general, data on the incidence of complications of RF‐versus CB‐based ablation and more complex ablation as compared with stand‐alone PVI are conflicting. While several studies have shown similar complication rates for more complex ablation strategies, 3,4,10 others describe enhanced rates of cardiac tamponade 11 or of minor and major complications in general 12 . Furthermore, PVI guided by balloon systems might be associated with a lower risk of tamponades as compared to point‐by‐point RF‐ablation 11 .…”
Section: Discussionmentioning
confidence: 92%
“…A study by Kany et al found that patient satisfaction was similar after primary and reablation procedures. 19 This leads to the conclusion…”
Section: Patient Satisfaction With Treatmentmentioning
confidence: 86%
“…A study by Kany et al found that patient satisfaction was similar after primary and reablation procedures. 19 This leads to the conclusion that at least in the group of patients with pAF postinterventional AAD might reduce treatment satisfaction. Patients with persAF are possibly more used to medication use (due to a higher number of comorbidities) and were not so much bothered by additional drug treatment.…”
Section: Discussionmentioning
confidence: 99%